2019
DOI: 10.14233/ajchem.2019.21716
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Synthesis of 1,5-Benzothiazepines Using Greener Reaction Medium

Abstract: An efficient and eco-friendly synthesis of 1,5-benzothiazepines has been developed by the reaction of various 2-propen-1-ones with 2-aminothiophenol using microwave irradiation in greener reaction medium, glycerol. The clean reaction conditions, shorter reaction time, high yields and non-toxic, biodegradable reaction medium manufactured from renewable sources are unique features of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…After isolation through extraction, the pure product 66 was obtained by recrystallization (Figure 20 ). [68] …”
Section: Synthetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After isolation through extraction, the pure product 66 was obtained by recrystallization (Figure 20 ). [68] …”
Section: Synthetic Methodsmentioning
confidence: 99%
“…After isolation through extraction, the pure product 66 was obtained by recrystallization (Figure 20). [68] In a last microwave-promoted example, an approach using water as the solvent has been described by Kendre 21). [69] These microwave-assisted reactions certainly contribute to green chemistry, because they use little to no solvent, proceed quickly and generally lead to better yields as compared to conventional alternatives.…”
Section: Synthesis Of 15-benzothiazepanes Through Reaction Of αβUnsat...mentioning
confidence: 99%
“…The microwave irradiation (MW) procedure is a prevailing tool in the 'green organic synthesis' for drug discovery [144,145]. The solvent-free and catalyst-free condition was also conducted under microwave for the condensation reaction to improve feasibility for numerous functional groups [146].…”
Section: S C H E M E 1 Synthesis Of Homocyclic-benzoheterodiazepine Derivativesmentioning
confidence: 99%
“…Eco-friendly conditions, short reaction time, and high yield were the key features of this synthetic protocol. [21] Lingampalle et al reported an environmentally benign one-pot protocol for the synthesis of 1,5-benzothiazepines (3) from 1,3-diarylpropene-1-ones (2) and o-aminothiophenol (1, Scheme 1, entry 2) via heating at 110 C in polyethylene glycol-400 (PEG −400). A comparative study between classical synthesis and this newly developed methodology was carried out, and it was evident from the results that the newer approach was better in terms of the yields of the final compounds after purification.…”
Section: Synthesis From Chalcones Using Eco-friendly Approachesmentioning
confidence: 99%